Combining confocal microscopy, dSTORM, and mass spectroscopy to unveil the evolution of the protein corona associated with nanostructured lipid carriers during blood–brain barrier crossing. Issue 36 (5th September 2022) - Battaglini, Matteo; Feiner, Natalia; Tapeinos, Christos; De Pasquale, Daniele; Pucci, Carlotta; Marino, Attilio; Bartolucci, Martina; Petretto, Andrea; Albertazzi, Lorenzo; Ciofani, Gianni
Abstract : Lipid magnetic nanovectors in contact with biological fluids are immediately covered by proteins. During the passage across brain endothelial cells, these proteins are partially lost and a new protein corona is developed. Abstract : Upon coming into contact with the biological environment, nanostructures are immediately covered by biomolecules, particularly by proteins forming the so-called "protein corona" (PC). The phenomenon of PC formation has gained great attention in recent years due to its implication in the use of nanostructures in biomedicine. In fact, it has been shown that the formation of the PC can impact the performance of nanostructures by reducing their stability, causing aggregation, increasing their toxicity, and providing unexpected and undesired nanostructure–cell interactions. In this work, we decided to study for the first time the formation and the evolution of PC on the surface of nanostructured lipid carriers loaded with superparamagnetic iron oxide nanoparticles, before and after the crossing of an in vitro model of the blood–brain barrier (BBB). Combining confocal microscopy, direct STochastic Optical Reconstruction Microscopy (dSTORM), and proteomic analysis, we were able to carry out a complete analysis of the PC formation and evolution. In particular, we highlighted that PC formation is a fast process, being formed around particles even after just 1 min of exposure to fetal bovine serum. Moreover, PC formed around particles is extremely heterogeneous: while some particles have no associated PC at all, others are completely covered by proteins. Lastly, the interaction with an in vitro BBB model strongly affects the PC composition: in particular, a large amount of the proteins forming the initial PC is lost after the BBB passage and they are partially replaced by new proteins derived from both the brain endothelial cells and the cell culture medium. Altogether, the obtained data could potentially provide new insights into the design and fabrication of lipid nanostructures for the treatment of central nervous system disorders.